Implementasi Program Taman Teknologi Pertanian (TTP) di Kecamatan Lebaksiu Kabupaten Tegal - Brian Pratama; Eny Lestari; Dwiningtyas Padmaningrum (Universitas Sebelas Maret, 2020)
By using George C Edward III’s policy implementation model, this study aimed to analyze the implementation of the ATP program from the perspective of stakeholders as program implementers which includes 1) the communication process carried out by the regional government 2) the support of allocated resources 3) the attitude tendencies of stakeholders 4) the bureaucratic structure that operates in the ATP program. This study used a qualitative approach with the descriptive method. The research location was determined by using a purposive method in Lebaksiu District, Tegal Regency, which is one of the 26 regions in Indonesia selected as the location of ATP development. The source of data used in this study were primary data and secondary data. The data collection technique carried out by in-depth interviews, documentation and observation. The data analysis was carried out in three stages, consisting of data reduction, data display and conclusion drawing. The results of the study showed that the implementation of the ATP program in Lebaksiu District has been running and is part of the Agriculture and Food Security office of Tegal Regency. The communication process that occurred has not been going well because of the unclear delivery of information, the continuity of communication has not occurred between stakeholders, and the ability of implementers to catch and understand information is also different. Support of allocated resources for ATP is still very minimal, both in human resources and budget resources. The attitude tendencies of stakeholders have been implemented quite well. The bureaucratic structure in the implementation of ATP in Lebaksiu is still not optimal because SOP has not yet been compiled.